2007
DOI: 10.1029/2007ja012492
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a bipolar magnetic signature in an earthward jet in the tail: Flux rope or 3D guide‐field reconnection?

Abstract: [1] Southward-then-northward magnetic perturbations are often seen in the tail plasma sheet, along with earthward jets, but the generation mechanism of such bipolar B z (magnetic flux rope created through multiple X-line reconnection, transient reconnection, or else) has been controversial. At $2313 UT on 13 August 2002, Cluster encountered a bipolar B z at the leading edge of an earthward jet, with one of the four spacecraft in the middle of the current sheet. Application to this bipolar signature of GradShaf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 31 publications
4
42
0
1
Order By: Relevance
“…The strong core field B y of these structures can be explained by three-dimensional (3-D) guide-field reconnection as demonstrated in magnetohydrodynamic (MHD) simulations by Shirataka et al (2006). Later, Hasegawa et al (2007) used the results of these MHD simulations for GS reconstruction analysis and showed that this technique can reconstruct flux ropes in the configurations without flux ropes being actually present. The latter means that one should be cautious when interpreting GS reconstruction results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong core field B y of these structures can be explained by three-dimensional (3-D) guide-field reconnection as demonstrated in magnetohydrodynamic (MHD) simulations by Shirataka et al (2006). Later, Hasegawa et al (2007) used the results of these MHD simulations for GS reconstruction analysis and showed that this technique can reconstruct flux ropes in the configurations without flux ropes being actually present. The latter means that one should be cautious when interpreting GS reconstruction results.…”
Section: Discussionmentioning
confidence: 99%
“…The latter means that one should be cautious when interpreting GS reconstruction results. Hasegawa et al (2007) summed up a guideline that can be used to distinguish flux ropes from a 3-D guide-field reconnection configuration. According to that guideline, the feature not typical for flux ropes is the presence of perpendicular velocity components in the HT frame, which is an indication of temporal variation of the structure, and plasma pressure enhancement in the leading part of the structure.…”
Section: Discussionmentioning
confidence: 99%
“…However, we do not rely on the topological property of the recovered field to infer if single or multiple X-lines were involved. This is because if the structure has some threedimensionality, the GSR method may lead to closed field loops in the 2D map even when there is in fact only single X-line [Hasegawa et al, 2007].…”
Section: Observations and Analysismentioning
confidence: 99%
“…The first FR was found by Amm et al (2006) to be tilted by ∼29 • from the GSM y-axis as seen from the +z-direction. The second signature, on the other hand, was discovered by Hasegawa et al (2007) to have been produced by a rather round FR oriented mainly in the y-direction, with a relaxed, approximately minimum-energy configuration. The tilt from the GSM y-axis as seen from the +z-direction was only ∼4 • .…”
Section: Auroral Emissionsmentioning
confidence: 99%
“…They suggested that this region of downward current, together with a trailing region of upward current further southwestward, might correspond to the ends of the flux rope. Recently, Hasegawa et al (2007) applied the Grad-Shafranov (GS, Sonnerup et al, 2006) reconstruction to the second FR. They deduced that the signature was most likely caused by a FR as opposed to, for instance, 3-D reconnection.…”
Section: Introductionmentioning
confidence: 99%